Physicochemical, thermal, rheological and morphological characteristics of flour and starch from a non-conventional source: Cucurbita foetidissima Kunth roots - Hernandez Centeno, Francisco; Rodriguez Gonzalez, Claudia; Lopez de la Peña, H.D.; Hernandez Gonzalez, M; Tirado Gallegos, J.M.; Rio Velasco, C; Zamudio Flores, P.B. (2020)
Starch is a biopolymer which demand has increased because of its multiple industrial applications. The present work was performed to characterize, both flour and starch obtained from Cucurbita foetidissima root as a non-conventional source. According to its physicochemical, rheological (flow curves), thermal and morphological properties. The flour was composed of a 77% total of carbohydrates, and the isolated starch showed 88% purity. Granules found in both samples exhibited birefringence and mixed morphology. Particle size distribution varied from 1 to 35 µm for flour and from 1 to 29 µm for starch. The k and n indices from their evaluated suspensions at 25, 50 and 70 °C indicated a non-Newtonian behavior of pseudoplastic type for both materials. Gelatinization temperature was 63.58 ± 3.08 °C with ΔH = 5.64 ± 3.81 J/g for flour, and of 66.50 ± 0.06 °C with ΔH = 12.27 ± 0.17 J/g for starch. XRD patterns were mixed A and B, characteristic of cereal starches and rubbers, with changes in the crystallinity percentage with each other. These materials characteristics are similar to those of other sources such as cassava (Manihot esculenta), but different from cereals as corn (Zea mays), and other tubers, as potato (Solanum tuberosum).